Assessing the relationship between FibroScan and laboratory parameters in evaluating hepatic fibrosis in patients with non-alcoholic fatty liver disease - Agrawal, Anmol; Malhotra, Y.; Patil, M.; Lakra, D. P.; Toppo, Archana (International Journal of Research in Medical Sciences, 2024)
Background: The gold standard for diagnosing steatosis, grading fibrosis, and determining its severity is liver biopsy (LB). An alternate, less expensive, and trouble-free technique for accurately identifying and measuring steatosis is the controlled attenuation parameter (CAP) value acquired with FibroScan.3 Hence, the present study was undertaken to correlate laboratory parameters (AST/ALT ratio, AST platelet ratio index, Fib-4 score) with FibroScan as a marker of hepatic fibrosis in non-alcoholic fatty liver disease (NAFLD) patients. Methods: 68 patients diagnosed to have NAFLD as per imaging were subjected to FibroScan using transient elastography within 2 weeks. Blood sample was taken for various lab tests. Area under receiver operating curve was plotted for predicting advanced fibrosis. Sensitivity and specificity were calculated. Results: Based on ROC curves of APRI, FIB-4, and AST/ALT ratio for the detection of F2 of liver fibrosis the best index to diagnose F2 from lower stages of liver fibrosis was APRI, with an AUROC curve of 0.747 (95% confidence interval [CI] 0.599–0.894). The optimal cut-off of APRI was 0.276 for this purpose, with a sensitivity of 70.83%, specificity of 79.55%, PPV of 65.38%, NPV of 83.3%, and DA of 76.47%. Conclusions: To conclude, it was found that the fibrosis stages increased significantly with APRI scores and Fib-4 score. AST/ALT ratio decreased with increase in FibroScan grade, however, mean of AST/ALT ratio was more in F2 grade than F1 with statistically non- significant relation. This can eliminate the need for LB in patients without clear indication.